SUHU DAN KELEMBABAN TANAH PADA TIGA PENGGUNAAN LAHAN DI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - Nurul Kamila Assolihat; Karyati Karyati; Muhammad Syafrudin (Fakultas Kehutanan Universitas Mulawarman, 2019)
The different land uses influence to the soil temperature and humidity in the different soil depths. The objective of this study was to know the soil temperature and humidity in the different soil depths (5 cm, 10 cm, 20 cm, and 30 cm) in three land uses (young secondary forest, settlement area, and open area). The average soil temperature in the young secondary forest were 27.6°C, 27.4°C, 27.0°C, dan 26.9°C. The average soil temperature in the soil depths of 5 cm, 10 cm, 20 cm, and 30 cm were 27.5°C, 27.4°C, 27.0°C, and 26.8°C in the settlement area. The average soil temperature in the open area were 27.6°C, 27.4°C, 27.0°C and 26.9°C. The average soil humidity in the young secondary forest were in depth of 5 cm, 10 cm, 20 cm and 30 cm were 78.5%, 78.8%, 79.1% and 79.4%. The average soil humidity in the settlement area were 76.4%, 78.5%, 79.3%, and 80.2% in the depths of 5 cm, 10 cm, 20 cm, and 30 cm. The average soil humidity in the depths of 5 cm, 10 cm, 20 cm, and 30 cm were 69.2%, 69.6%, 70.3%, dan 70.8% in the open area.